Intelligent and knowledge-based computing for business and organizational advancements - Sasaki, Hideyasu; Chiu, Dickson K. W. 1966-; Kapetanios, Epaminondas; Hung, Patrick C. K.; Andres, Frederic; Leung, Ho-Fung 1963-; Chbeir, Richard 1973- (Premier reference source, 2012)
"This book examines the emerging computing paradigm of Collective Intelligence (CI) and offers the computer and information science communities as it continue to move toward a new period of fully technology-integrated businesses" - Provided by publisher